Studi Kasus Terhadap Persiapan Mengajar Bagi Guru Sekolah Minggu Ditinjau dari Shared Christian Praxis [Case Study of Teaching Preparation of Sunday School Teachers Analyzed from Shared Christian Praxis] - Prastika, Erchia Chara (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
The existence of Sunday Schools is considered important for both the people and church leaders because a Sunday School is not just a place for our children to listen to the Bible stories. As a result, this study aims to describe, identify the struggles and analyze the obstacles of the Sunday School teachers to maintain consistency in their teaching preparations. A case study was used, involving 12 participants at the Indonesian Christian Church XYZ. The data were collected using the questionnaires and in-depth interviews and were triangulated using the coding system (Strauss & Corbin, 1989). The results have indicated that the Shared Christian Praxis helps the Sunday School teachers to maintain consistency in attending the collective teaching preparations, helps to transform their personal lives for the better ways of teaching, and also directs them to share their teaching experiences.